Ecoinovações no polo industrial de Manaus : direcionadores e fatores determinantes - Aloise, Pedro Gilberto (My University, 2017)
One of the points of relevance of the Report of the World Commission on Environment and Development of 1987 concerns the non-predatory use of natural resources and the degradation of the environment. Innovations emerge as a means to achieve these goals and organizations have an important role to play in this regard. Organizational studies on eco-innovation (EI) are concentrated in developed countries and the literature has recommended new research to analyze specific factors and conditions in developing countries. Following this recommendation, the research sought to identify the drivers of eco-innovations in the industries installed in the Industrial Pole of the Manaus Free Trade Zone and concomitantly the obstacles and orientation to the innovation of these organizations. From the methodological point of view the research was developed in the form of a case study, to be analyzed under the qualitative and quantitative perspectives.The qualitative and exploratory approach was developed through interviews and analyzed through content analysis. The quantitative approach was performed through a survey of a sample of industrial companies located in Manaus. The research contributes to eco-innovation theory Manaus Free Trade Zone, identifying regional drivers as proposed in previous studies. Amazonian biodiversity is considered the main potential factor that can guide eco-innovations, through the development of new products, through biotechnologies, biopharmaceuticals, bio-cosmetics and herbal medicines. Other identified drivers are related to changes in local legislation, resources for Research and Development, innovative courses, development of reverse technologies (reuse of waste in productive processes), environmental certification, competitiveness, creativity and business continuity. The most relevant difficulties and obstacles are related to the disarticulation between companies, academia and government bodies due to the lack of a structured innovation system and a consolidated innovation model. Other obstacles stem from economic and managerial problems, cultural, operational and political reasons. Finally, the research provided insights for the proposal of future studies related to drivers of eco-innovations, deficiencies and obstacles to the consolidation of innovation systems and their impacts on the development of new products and processes, obstacles to integration among the agents of the triple helix (universisties companies, and government) and its reflections on the development of innovations, orientation and obstacles to innovation related to organizational performance (financial, technological and environmental).
Um dos pontos de relevância do Relatório da Comissão Mundial do Meio Ambiente e Desenvolvimento, de 1987 diz respeito a utilização não predatória dos recursos naturais e com a degradação do meio ambiente. As inovações surgem como meio de se atingir estes objetivos e as organizações tem um importante papel a cumprir neste sentido. Os estudos organizacionais sobre ecoinovação (EI) estão concentrados em países desenvolvidos e a literatura tem recomendado novas pesquisas para se analisar fatores e condições específicas em países em desenvolvimento. Seguindo esta recomendação a pesquisa buscou identificar os direcionadores de ecoinovações, nas indústrias instaladas no Polo Industrial da Zona Franca de Manaus e concomitantemente os obstáculos e orientação à inovação dessas organizações. Do ponto de vista metodológico a pesquisa se desenvolveu sob a forma de estudo de caso, a ser analisado sob as perspectivas qualitativa e quantitativa. A abordagem qualitativa e exploratória foi desenvolvida através de entrevistas e analisadas por meio de análise de conteúdo. A abordagem quantitativa foi realizada por meio de survey em uma amostra de empresas industriais instaladas em Manaus. A pesquisa contribui com a teoria de ecoinovação na Zona Franca de Manaus, identificando direcionadores regionais de ecoinovação conforme proposto em estudos anteriores. A biodiversidade amazônica é o principal fator potencial que pode direcionar ecoinovações, através do desenvolvimento de novos produtos, por meio de biotecnologias, biofármacos, biocosméticos e fitoterápicos (plantas medicinais). Outros direcionadores identificados estão relacionados às mudanças na legislação local, recursos para Pesquisa e Desenvolvimento, cursos inovadores, desenvolvimento de processos reversos (reutilização de resíduos em processos produtivos), certificação ambiental, competitividade, criatividade e continuidade dos negócios. As dificuldades e obstáculos mais relevantes estão relacionados à desarticulação entre empresas, academia e órgãos governamentais decorrentes da falta de um sistema de inovação estruturado e de um modelo de inovação consolidado. Outros entraves decorrem de problemas de natureza econômica e gerencial, razões de ordem cultural, operacional e política. Por fim, a pesquisa proporcionou insights para a proposição de estudos futuros relacionados a direcionadores de ecoinovações, deficiências e entraves à consolidação dos sistemas de inovação e seus impactos sobre o desenvolvimento de novos produtos e processos, obstáculos a integração entre os agentes da tríplice hélice (academia, empresas e governo) e seus reflexos sobre o desenvolvimento de inovações, orientação e obstáculos a inovação relacionados com a performance organizacional (performance, financeira, tecnológica e ambiental).
Keywords: Administração; Inovação; Sustentabilidade; Criatividade; Meio ambiente; Management; Innovation; Sustainability; Creative ability; Environment